Slownik szkolny : terminy i pojecia historyczne - Snoch, Bogdan (Warszawa : Wydawnictwa Szkolne i Pedagogiczne, 1992)
A dictionary of historical terms for high school students. Ages 13-18.
Includes bibliographical references (p. [204]).
Keywords: History -- Dictionaries -- Polish